Highly Basic Clusters in the Herpes Simplex Virus 1 Nuclear Egress Complex Drive Membrane Budding by Inducing Lipid Ordering - Michael K. Thorsen (American Society for Microbiology, 2021)
ABSTRACT During replication of herpesviruses, capsids escape from the nucleus into the cytoplasm by budding at the inner nuclear membrane. This unusual process is mediated by the viral nuclear egress complex (NEC) that deforms the membrane around the capsid by oligomerizing into a hexagonal, membrane-bound scaffold. Here, we found that highly basic membrane-proximal regions (MPRs) of the NEC alter lipid order by inserting into the lipid headgroups and promote negative Gaussian curvature. We also find that the electrostatic interactions between the MPRs and the membranes are essential for membrane deformation. One of the MPRs is phosphorylated by a viral kinase during infection, and the corresponding phosphomimicking mutations block capsid nuclear egress. We show that the same phosphomimicking mutations disrupt the NEC-membrane interactions and inhibit NEC-mediated budding in vitro, providing a biophysical explanation for the in vivo phenomenon. Our data suggest that the NEC generates negative membrane curvature by both lipid ordering and protein scaffolding and that phosphorylation acts as an off switch that inhibits the membrane-budding activity of the NEC to prevent capsid-less budding. IMPORTANCE Herpesviruses are large viruses that infect nearly all vertebrates and some invertebrates and cause lifelong infections in most of the world’s population. During replication, herpesviruses export their capsids from the nucleus into the cytoplasm by an unusual mechanism in which the viral nuclear egress complex (NEC) deforms the nuclear membrane around the capsid. However, how membrane deformation is achieved is unclear. Here, we show that the NEC from herpes simplex virus 1, a prototypical herpesvirus, uses clusters of positive charges to bind membranes and order membrane lipids. Reducing the positive charge or introducing negative charges weakens the membrane deforming ability of the NEC. We propose that the virus employs electrostatics to deform nuclear membrane around the capsid and can control this process by changing the NEC charge through phosphorylation. Blocking NEC-membrane interactions could be exploited as a therapeutic strategy.